Error quantification in pharmacokinetic parameters derived from DCE-MRI data using a novel anthropomorphic dynamic prostate phantom. Issue 7 (July 2016) - Knight, Silvin P.; Browne, Jacinta E.; Meaney, James F.; Smith, David S.; Fagan, Andrew J.
Abstract : Pharmacokinetic (PK) modelling of dynamic contrast enhanced (DCE) MRI data has shown considerable promise in the detection of many cancers, including prostate. However, the clinical implementation of DCE-MRI acquisition protocols suitable for PK modelling has been greatly hindered by the lack of consistency with published PK parameter values, such as the volume-transfer constant ( K trans ), with widely varying acquisition protocols and PK modelling approaches adding to the confusion. A novel anthropomorphic dynamic prostate phantom has been developed to address this shortcoming. The device is capable of simultaneously producing two distinct contrast time-intensity curves (CTCs), representative of those observed in DCE-MRI data from healthy and tumorous prostate tissue, in an environment which closely mimics the male pelvic region. CTCs were measured using a custom-built optical scanner, and 'ground truth' PK parameter values derived from the data. DCE-MRI data were acquired using a 3T scanner (Achieva, Philips, Netherlands) and a 16-channel phased array detector coil (3D-SPGR, TR/TE = 3.6/1.75 ms, flip = 10°, voxel size = 1.1 × 1.1 × 4 mm 3, FOV = 224 × 224 × 72 mm 3, slices = 18). The parallel imaging factor and number of signal averages were varied to give temporal resolutions from 2.3 s to 20.3 s. K trans values derived from MR data from the phantom were compared with the ground truth values and were found to differ by −8.1% to −44.6%, with the lowest variance from ground truth values achieved at a temporal resolution of 6.8 s. The phantom provides a model system on which the quantitative validation of new prostate DCE-MRI protocols can be performed, and could contribute to the standardisation of clinical prostate DCE-MRI acquisition protocols.